Neurological complications in pediatric patients with SARS-CoV-2 infection: a systematic review of the literature - L. Siracusa; A. Cascio; S. Giordano; A. A. Medaglia; G. A. Restivo; I. Pirrone; G. F. Saia; F. Collura; C. Colomba (BMC, 2021)
Abstract Objectives To describe clinical characteristics, laboratory tests, radiological data and outcome of pediatric cases with SARS-CoV-2 infection complicated by neurological involvement. Study design A computerized search was conducted using PubMed. An article was considered eligible if it reported data on pediatric patient(s) with neurological involvement related to SARS-CoV-2 infection. We also described a case of an acute disseminated encephalomyelitis (ADEM) in a 5-year-old girl with SARS-CoV-2 infection: this case was also included in the systematic review. Results Forty-four articles reporting 59 cases of neurological manifestations in pediatric patients were included in our review. Most (32/59) cases occurred in the course of a multisystem inflammatory syndrome in children (MIS-C). Neurological disorders secondary to cerebrovascular involvement were reported in 10 cases: 4 children with an ischemic stroke, 3 with intracerebral hemorrhage, 1 with a cerebral sinus venous thrombosis, 1 with a subarachnoid hemorrhage, 1 with multiple diffuse microhemorrhages. Reversible splenial lesions were recognized in 9 cases, benign intracranial hypertension in 4 patients, meningoencephalitis in 4 cases, autoimmune encephalitis in 1 girl, cranial nerves impairment in 2 patients and transverse myelitis in 1 case. Five cases had Guillain-Barré syndrome (GBS) and two, including ours, had ADEM. Radiological investigations were performed in almost all cases (45/60): the most recurrent radiological finding was a signal change in the splenium of the corpus callosum. The presence of SARS-CoV-2 viral nucleic acid in the cerebrospinal fluid was proved only in 2 cases. The outcome was favorable in almost all, except in 5 cases. Conclusions Our research highlights the large range of neurological manifestations and their presumed pathogenic pathways associated with SARS-CoV-2 infection in children. Nervous system involvement could be isolated, developing during COVID-19 or after its recovery, or arise in the context of a MIS-C. The most reported neurological manifestations are cerebrovascular accidents, reversible splenial lesions, GBS, benign intracranial hypertension, meningoencephalitis; ADEM is also a possible complication, as we observed in our patient. Further studies are required to investigate all the neurological complications of SARS-CoV-2 infection and their underlying pathogenic mechanism.